"Taalkundige" eksegese van romeine 13 :1 - 7 - Botha, J. (Koers, 1988)
As in most scientific disciplines, theoretical and methodological developments in recent times are constantly changing and greatly influencing New Testament studies. The aim of this article is to illustrate, with the use of modern exegetical methods, a possible approach to the "linguistic" phase of the exegetical process. The approach encompasses seven steps, namely, (1) demarcation of the periscope for investigation, (2) a literal translation, (3) grammatical and syntactical commentary, (4) a text -critical check of important variant readings, (5) discourse analysis, (6) a visual representation of the place of the periscope within its broader textual context and (7) word study. Romans 13 :1-7 (which deals with obedience to the authorities) is used for the illustration of all seven these methodological steps. As conclusion it is stated that although this approach does not solve all the exegetical and hermeneutical problems of the periscope (which, however, it also does not pretend to do) , these seven things will always remain an essential pa r t of the basic exegetical work in a scientific interpretation of New Testament texts .